Marathon Health Pitfalls: What Every Runner Needs to Know - Gondko, Daniel; Dębiec, Patrycja; Roman, Jakub; Pietrzak, Nikodem (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Long-distance running, especially marathons, tests human endurance and physical limits. While the benefits of marathon running are well-documented, the associated health risks often go unnoticed. This review aims to synthesize current knowledge on the health risks and complications faced by marathon runners, providing crucial insights for both amateur and professional athletes. State of Knowledge: Marathon running imposes significant stress on the cardiovascular system, musculoskeletal structure, and metabolic processes. Issues such as acute myocardial injury, overhydration leading to hyponatremia, and musculoskeletal injuries are prevalent. The review also examines less common but severe risks like rhabdomyolysis and marathon-related cardiac arrests. Despite the robust fitness levels of runners, these health risks remain a serious concern, necessitating preventive strategies and proper health monitoring. Summary: Marathon runners must be aware of the potential health risks associated with prolonged endurance activities. Precautionary measures, including tailored training programs, dietary adjustments, and regular medical check-ups, are essential to mitigate these risks. Additionally, further research is required to develop more effective interventions and guidelines that can safeguard the health of marathon participants. This review underscores the need for a balanced approach that respects the physiological demands of marathon running while ensuring the health and safety of the runners.